2019
DOI: 10.1007/s12253-019-00600-9
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression and Promoter Hypermethylation of the Tumour Suppressor SLIT2, are Associated with Adverse Patient Outcomes in Diffuse Large B Cell Lymphoma

Abstract: SLIT2 has been classified as a major tumour suppressor gene due to its frequent inactivation in different cancer types. However, alterations of SLIT2 expression and relation to patient outcomes in diffuse large B-cell lymphoma (DLBCL) remain undefined. The aim of this study was to investigate the expression and the methylation status of SLIT2 gene as well as its relation to patient outcomes in DLBCL. Immunohistochemical (IHC) staining was carried out to detect the expression of SLIT2 in a series of 108 DLBCL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In line with this finding, low SLIT2 expression in DLBCL was previously shown to correlate with an advanced clinical stage and shorter OS. 17 Similarly, in non-haematological cancers, loss of tumoral SLIT2 enhanced metastasis, leading to cancer progression and shorter survival. 13…”
Section: Resultsmentioning
confidence: 99%
“…In line with this finding, low SLIT2 expression in DLBCL was previously shown to correlate with an advanced clinical stage and shorter OS. 17 Similarly, in non-haematological cancers, loss of tumoral SLIT2 enhanced metastasis, leading to cancer progression and shorter survival. 13…”
Section: Resultsmentioning
confidence: 99%
“…Independent validation across different cohorts is of great importance for biomarker development, and OSdlbcl is a web server that could facilitate the cross‐validation of the prognostic value of biomarkers across seven DLBCL cohorts. To determine the prognosis performance of OSdlbcl, we collected 23 previously published DLBCL prognostic factors at the mRNA or protein level and tested their prognostic power in OSdlbcl at the mRNA level (Table , Figure ) . The forest plots more effectively presented the comparison results from references and OSdlbcl (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the prognosis performance of OSdlbcl, we collected 23 previously published DLBCL prognostic factors at the mRNA or protein level and tested their prognostic power in OSdlbcl at the mRNA level (Table 2, Figure 1). 2,9,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The forest plots more effectively presented the comparison results from references and OSdlbcl ( Figure S1). Results showed that about 52% (12 out of 23) of biomarkers have significant prognostic values in the combined cohorts, while the remaining biomarkers (11 out of 23) present significant prognostic values in one or more cohorts ( Table 2).…”
Section: Evaluation Of Previously Reported Dlbcl Prognostic Biomarkmentioning
confidence: 98%
“…Recent studies indicated that SLIT2 is frequently inactivated in large B-cell lymphoma (36), lung, breast, colorectal, thyroid (37), gastric (38), and glioma tumors, showing that SLIT2 was a candidate tumor suppressor gene, and recent studies have shown that SLIT2 expression is suppressed or reduced by hypermethylation in the promoter region in various cancers. Tavora showed that deleting endothelial SLIT2 suppressed metastatic dissemination in mouse models of breast and lung cancer (39).…”
Section: Discussionmentioning
confidence: 99%